Acceptability of community based participatory action research (CPAR) corn-based technology among farmers in Barangay Sto. Niño, Capoocan, Leyte - Sultan, Nenita G (Iloilo City U.P. in the Visayas, 2007)
The study aims to determine the acceptability of CPAR Corn-Based technology among farmers in Brgy. Sto. Niño, Capoocan Leyte. The respondents are the twenty (20) farmer beneficiaries who adopted the introduced technology from Crop year 2003-2006. The selection of the respondents was done in coordination with the Project management; the OPA-Research Division staff and personnel and the members of the Provincial Technology Verification Team (PTVT). An interview schedule was used in gathering primary data. The data were encoded, tabulated, and analyzed using descriptive statistical tools such as frequency distribution and percentages.. All the respondents are married and majority are male. The age group ranges from 35-65 years old. Many are farmers who are tenants of the land they till. Farming is the primary source of income of two-thirds or 65% of the respondents. Many of them (85%) have been farming for over 20 years. All of them claim that the introduction of the CPAR Corn-bases technology has significantly affected their economic status. The adoption of the introduced technology resulted in increased yield and income. They also claim that there was an additional income derived from the adoption of other component technologies such as peanut and swine production and these contribute to the overall performance of the enterprise. among the problems identified t have significant effects on the success of farmers relative to production and income is tenurial status. This is typified by the very limited intervention that hey can introduce to the land because the landowner often dictates the crop to be planted and land use pattern to be followed. Recommendattions of the respondents include genuine policy reforms and advocacy by the government in resolving the problem on tenurial status wherein 90% of the respondents signified their intention to own the land for them to optimize the effect of the CPAR Technology and harness the land's true potential.
"Final report (Research Methods in Management)"